Предмет: Алгебра,
автор: Evgeniysan
Помогите решить уравнения:
1)2х+3(1-х)=5х
2)4х+(5х-1)=3(2х+1)
Ответы
Автор ответа:
1
1.2х+3*1-3*х=5х
2х+3-3х=5х
2х-3х-5х=-3
-6х=-3
х=(-3)/(-6)
х=1/2
2.4х+5х-1=3*2х+3*1
4х+5х-1=6х+3
4х+5х-6х=3+1
3х=4
х=4/3=1 1/3
2х+3-3х=5х
2х-3х-5х=-3
-6х=-3
х=(-3)/(-6)
х=1/2
2.4х+5х-1=3*2х+3*1
4х+5х-1=6х+3
4х+5х-6х=3+1
3х=4
х=4/3=1 1/3
Похожие вопросы
Предмет: Физкультура и спорт,
автор: iasmina1809
Предмет: Алгебра,
автор: doshigg
Предмет: Геометрия,
автор: verba20072016
Предмет: Биология,
автор: 8341458
Предмет: Математика,
автор: Королева20031